Synthesis and Pharmacological Screening of Indan-1-propionic Acids as Anti-hypercholesterolemic Agents - Adak, M.R. (Asian Journal of Chemistry, 2010)
Non-methoxy and methoxy indan-1-propionic acids have been synthesized from their corresponding benzaldehyde via indan-1-acetic acids as intermediate. The chemical structures of the proposed compounds were established based on 1H NMR and IR spectral data. The synthesized compounds were screened for anti-hypercholesterolemic activity in male albino Charles Forster rats at 50 mg/kg dose. Dimethoxy substi-tuted indan-1-propionic acid (compound 3) showed better activity profile than their homologues but none of them was found in superior to standard drug clofibrate.